Fragment-based discovery of a potent NAMPT inhibitor. Issue 3 (1st February 2018) - Korepanova, Alla; Longenecker, Kenton L.; Pratt, Steve D.; Panchal, Sanjay C.; Clark, Richard F.; Lake, Marc; Gopalakrishnan, Sujatha M.; Raich, Diana; Sun, Chaohong; Petros, Andrew M.
Graphical abstract: Abstract: NAMPT expression is elevated in many cancers, making this protein a potential target for anticancer therapy. We have carried out both NMR based and TR-FRET based fragment screens against human NAMPT and identified six novel binders with a range of potencies. Co-crystal structures were obtained for two of the fragments bound to NAMPT while for the other four fragments force-field driven docking was employed to generate a bound pose. Based on structural insights arising from comparison of the bound fragment poses to that of bound FK866 we were able to synthetically elaborate one of the fragments into a potent NAMPT inhibitor.